ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI, DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Dinas Pendidikan Provinsi Jawa Tengah) - Pradipto, Sindu; Rahardja, Edy (Diponegoro Journal of Management, 2015)
This study aimed to analyze the influence of leadership style on employee performance Education Office of Central Java province, to analyze the influence of labor discipline on employee performance Education Office of Central Java province, to analyze the influence of leadership style on job motivation of Education Office of Central Java province, to analyze the influence of labor discipline on work motivation Education Office of Central Java province, to analyze the effect of work motivation on employee performance Education Office of Central Java province.The sample was 54 employees in Central Java Provincial Education Department, with technical distributing questionnaires then tested the validity, reliability test, the classic assumption test and regression analysis to test the hypothesis.Based on the analysis and discussion, it can be concluded that: (1)leadership style significantly positive effect on employee performance so the first hypothesis is accepted. That is the better style of leadership will further improve the performance of employees. (2) Discipline labor significantly positive effect on employee performance so the second hypothesis is accepted. This means that the better work discipline will further improve the performance of employees. (3) The style of leadership in a positive and significant effect on work motivation. So the better style of leadership, the higher motivation to work so that the third hypothesis is accepted. (4) The discipline of working in a positive and significant effect on work motivation. So the higher the discipline of work, the higher motivation to work so that the fourth hypothesis is accepted. (5) work motivation significantly positive effect on employee performance. So the fifth hypothesis is accepted. This means that the higher work motivation will further improve the performance of employees.